Transcriptome and Metabolome Integration Provides New Insights Into the Regulatory Networks of Tibetan Pig Alveolar Type II Epithelial Cells in Response to Hypoxia - Yang, Yanan; Yuan, Haonan; Liu, Xuanbo; Wang, Zhengwen; Li, Yongqing; Ren, Yue; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Genetics, 2022)
Tibetan pigs show a widespread distribution in plateau environments and exhibit striking physiological and phenotypic differences from others pigs for adaptation to hypoxic conditions. However, the regulation of mRNAs and metabolites as well as their functions in the alveolar type II epithelial (ATII) cells of Tibetan pigs remain undefined. Herein, we carried out integrated metabolomic and transcriptomic profiling of ATII cells between Tibetan pigs and Landrace pigs across environments with different oxygen levels to delineate their signature pathways. We observed that the differentially accumulated metabolites (DAMs) and differentially expressed genes (DEGs) profiles displayed marked synergy of hypoxia-related signature pathways in either Tibetan pigs or Landrace pigs. A total of 1470 DEGs between normoxic (TN and TL) and hypoxic (TL and LL) groups and 240 DEGs were identified. Functional enrichment assessment indicated that the hypoxia-related genes and metabolites were primarily involved in glycolysis and aldosterone synthesis and secretion. We subsequently constructed an interaction network of mRNAs and metabolites related to hypoxia, such as guanosine-3', 5'-cyclic monophosphate, Gly-Tyr, and phenylacetylglycine. These results indicated that MAPK signaling, aldosterone synthesis and secretion, and differences in the regulation of MCM and adenosine may play vital roles in the better adaptation of Tibetan pigs to hypoxic environments relative to Landrace pigs. This work provides a new perspective and enhances our understanding of mRNAs and metabolites that are activated in response to hypoxia in the ATII cells of Tibetan pigs.